Emic components of well-being. Towards an alternative development model - Yamamoto, Jorge (2007)
An alternative model of well-being and development using an emic and post-hoc approach is presented. This method was applied to a non-educated corridor sample which includes rural and urban shantytowns (n = 550). A psychometric wellbeing battery was developed for this study. Analytical technique includes a modified version of Confirmatory Factor Analysis in order to meet the demands of the post-hoc theorisation rationale. Alternative models of universal needs, subjective life satisfaction, resources, and values are presented. A three factor personality solution is described. Discussion emphasises the advantages of these results compared to theories and approaches from Europe and United States in theoretical and empirical terms. Implications for development are also discussed.